Urban soil carbon and nitrogen converge at a continental scale. Issue 2 (27th January 2020) - Trammell, Tara L. E.; Pataki, Diane E.; Pouyat, Richard V.; Groffman, Peter M.; Rosier, Carl; Bettez, Neil; Cavender‐Bares, Jeannine; Grove, Morgan J.; Hall, Sharon J.; Heffernan, James; Hobbie, Sarah E.; Morse, Jennifer L.; et al.
Abstract: In urban areas, anthropogenic drivers of ecosystem structure and function are thought to predominate over larger‐scale biophysical drivers. Residential yards are influenced by individual homeowner preferences and actions, and these factors are hypothesized to converge yard structure across broad scales. We examined soil total C and total δ 13 C, organic C and organic δ 13 C, total N, and δ 15 N in residential yards and corresponding reference ecosystems in six cities across the United States that span major climates and ecological biomes (Baltimore, Maryland; Boston, Massachusetts; Los Angeles, California; Miami, Florida; Minneapolis‐St. Paul, Minnesota; and Phoenix, Arizona). Across the cities, we found soil C and N concentrations and soil δ 15 N were less variable in residential yards compared to reference sites supporting the hypothesis that soil C, N, and δ 15 N converge across these cities. Increases in organic soil C, soil N, and soil δ 15 N across urban, suburban, and rural residential yards in several cities supported the hypothesis that soils responded similarly to altered resource inputs across cities, contributing to convergence of soil C and N in yards compared to natural systems. Soil C and N dynamics in residential yards showed evidence of increasing C and N inputs to urban soils or dampened decomposition rates over time that are influenced by climate and/or housing age across the cities. In the warmest cities (Los Angeles, Miami, Phoenix), greater organic soil C and higher soil δ 13 C in yards compared to reference sites reflected the greater proportion of C4 plants in these yards. In the two warm arid cities (Los Angeles, Phoenix), total soil δ 13 C increased and organic soil δ 13 C decreased with increasing home age indicating greater inorganic C in the yards around newer homes. In general, soil organic C and δ 13 C, soil N, and soil δ 15 N increased with increasing home age suggesting increased soil C and N cycling rates and associated 12 C and 14 N losses over time control yard soil C and N dynamics. This study provides evidence that conversion of native reference ecosystems to residential areas results in convergence of soil C and N at a continental scale. The mechanisms underlying these effects are complex and vary spatially and temporally.